2020
DOI: 10.20473/ovz.v8i2.2019.94-99
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Umur Dengan Calving Interval, Days Open, Dan Service Per Conseption Sapifriesian Holstein (Fh)

Abstract: The purpose of this research was to know the relationship between age with calving inteval (CI), days open (DO), and service per conception (S/C) in Friesian Holstein dairy cattle (FH). The research was started on Desember 2017 to January 2018 in PT. Greenfields Indonesia partnerships, KecamatanWagir Kabupaten Malang. The materials of the search used were 100 heads of dairy cattle which had at least two times of parturition. The method used in this research was a survey and data collection. The data were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
1
6
0
3
Order By: Relevance
“…Retno et al [25] reported that the value of S/C was also influenced by age, where the reproduction of old cattle experienced a decline in reproductive efficiency. The same thing was reported by Ananda et al [9] that increasing age in the animal is followed by an increase in the value of S/C.…”
Section: Service Per Conceptionsupporting
confidence: 85%
See 1 more Smart Citation
“…Retno et al [25] reported that the value of S/C was also influenced by age, where the reproduction of old cattle experienced a decline in reproductive efficiency. The same thing was reported by Ananda et al [9] that increasing age in the animal is followed by an increase in the value of S/C.…”
Section: Service Per Conceptionsupporting
confidence: 85%
“…Reproduction is related to the production aspect of livestock, there is production if the reproduction process is going well [8]. Therefore, reproductive efficiency in the livestock business is very important and becomes a benchmark for livestock success [9]. The high and low reproductive efficiency of cattle can be measured using the parameters Service Per Conception (S/C) and Conception Rate (CR) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The calving interval is the time between one birth and the next birth, where the optimal calving interval of Bali cows is around 12 months or 1 year. (Ananda et al, 2020).…”
Section: Calving Interval (Ci)mentioning
confidence: 99%
“…This is because breeding is an important production factor in the cultivation of Bali cattle. After all, quality seedlings can influence beef production (Sousa et al 2017;Ananda et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini berhubungan dengan profil ekspresi gen yang berubah dan penurunan jumlah salinan DNA mitokondria (mtDNA), sehingga oosit mengalami apoptosis (Ferreira et al, 2016), menyebabkan kegagalan pembuahan atau kegagalan perkembangan embrio yang diakhiri dengan kematian embrio dini, dan kegagalan kebuntingan. Terdapat hubungan antara S/C dengan calving interval pada sapi perah Friesian Holstein (Ananda et al, 2019). Dengan demikian semakin tinggi nilai S/C dapat memperpanjang CI, sehingga target untuk mendapatkan anak sapi setahun sekali tiak tercapai.…”
Section: Services Per Conceptionunclassified